1979
DOI: 10.1111/j.1600-051x.1979.tb01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival microflora of periodontal patients on tetracycline therapy

Abstract: Samples of subgingival plaque were collected from periodontal patients receiving two different tetracycline treatment regimens following conventional periodontal therapy. Four patients had received an oral dose of 1000 mg/day for 2 weeks and nine had received 1000 mg/day for 1 week followed by 250 mg/day for extended time periods. The latter regimen is similar so that commonly prescribed for the chronic skin disease, acne vulgaris. Taxonomic characterization of plaque isolates indicated that the predominant or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 17 publications
1
42
1
Order By: Relevance
“…In these latter investigations, the patients were treated by conventional means before antibiotic therapy, and attempts were made to isolate anaerobes, as well as the total facultative population, from periodontal pockets. The results suggested that after a 2-week tetracycline regimen, streptococci predominated (39). However, a much greater microbial complexity was observed, including resistant gramnegative subgingival organisms, when the antibiotic was administered for extended periods of time (34,39).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In these latter investigations, the patients were treated by conventional means before antibiotic therapy, and attempts were made to isolate anaerobes, as well as the total facultative population, from periodontal pockets. The results suggested that after a 2-week tetracycline regimen, streptococci predominated (39). However, a much greater microbial complexity was observed, including resistant gramnegative subgingival organisms, when the antibiotic was administered for extended periods of time (34,39).…”
Section: Resultsmentioning
confidence: 87%
“…The results suggested that after a 2-week tetracycline regimen, streptococci predominated (39). However, a much greater microbial complexity was observed, including resistant gramnegative subgingival organisms, when the antibiotic was administered for extended periods of time (34,39). A primary objective of this study was to determine the extent of plasmid-associated tetracycline resistance within the oral streptococcal flora.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these bacteria, like other anaerobes, are susceptible to various antimicrobials; however, several of these species are resistant to tetracycline. In periodontal patients undergoing therapy, Veillonella species, along with Streptococcus and Neisseria species, were found to be consistently resistant to tetracycline (30). Moreover, tetracycline-resistant Veillonella species have the opportunity to come in close contact with and, consequently, transfer resistance elements to other oral bacteria and the bacteria that pass through the oral cavity (31).…”
mentioning
confidence: 99%
“…Periodontol., in press) have shown that tetracycline is delivered in sufficient quantities to inhibit most organisms at the site of infection, which in periodontal diseases is the pocket or space between the teeth and the gingiva. However, resistance to this drug is not uncommon (15,18) and may account for patients who continue to lose alveolar bone despite conventional therapy and the adjunctive use of tetracycline. In some patients, susceptibility data have indicated that penicillin may be as effective as tetracycline (7,15).…”
mentioning
confidence: 99%